2016
DOI: 10.1177/1043659616676318
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experiences of Novice Male Nurses in Taiwan

Abstract: This study addresses masculinity issues and gender stereotyping. In addition, male nurses were very concerned about their career options and development and the likelihood of promotion. This research not only has implications for better understanding of novice male nurses' needs and the challenges in their social life but also makes suggestions for nursing practice to attract and keep more male nurses in the nursing profession. The results illustrate how culturally congruent nursing care can be achieved when w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 27 publications
2
71
0
Order By: Relevance
“…Most male nurses/midwives are unhappy if they deliver less advanced care. Thus, immediately after deployment to the professional practice, male nurses/midwives typically concentrate on delivering a good standard of service and earning a promotion [13, 16, 27]. This possibly helps them overlook essential cares less frequently than their female counterparts [13, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Most male nurses/midwives are unhappy if they deliver less advanced care. Thus, immediately after deployment to the professional practice, male nurses/midwives typically concentrate on delivering a good standard of service and earning a promotion [13, 16, 27]. This possibly helps them overlook essential cares less frequently than their female counterparts [13, 16].…”
Section: Discussionmentioning
confidence: 99%
“…There is limited research on the working experiences of male nurses in mainland China (Bai, Li, & Sun, 2005). While studies about male nurses in Taiwan (Cheng, Tseng, Hodges, & Chou, 2018;Liu & Li, 2017;Yang et al, 2004), Hong Kong (Chan, Chan, Yu, Law, Woo, & Lam, 2014)…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…There is limited research on the working experiences of male nurses in mainland China (Bai, Li, & Sun, ). While studies about male nurses in Taiwan (Cheng, Tseng, Hodges, & Chou, ; Liu & Li, ; Yang et al, ), Hong Kong (Chan, Chan, Yu, Law, Woo, & Lam, ) and Western countries can shed light on the situation of male nurses in mainland China, unique education and health care systems, along with different cultural contexts, could lead to distinctive working experiences among male nurses in mainland China. A holistic understanding of the working experiences and career trajectories of Chinese male nurses can help us to devise strategies to recruit and retain male nurses and alleviate the nursing shortage in China, especially in light of the challenges posed by demographic ageing.…”
Section: Introductionmentioning
confidence: 99%
“…There are also differences in male nurse proportions in some of the Chinese culture influenced regions of Eastern Asia. In Taiwan, males accounted for 2.06% of the nursing workforce in 2016 [6], while in Hong Kong, 13.4% of the active registered nurses were males in 2016 [7]. More research is needed to explore why gender disparity still exists in nursing and why the discrepancy is more significant in some countries and regions than others.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found various barriers men encounter when they choose nursing [6,8]. Male nurses are often considered to be unsuitable caregivers.…”
Section: Introductionmentioning
confidence: 99%